Futureproof Competition Law - Gerbrandy, Anna (Eleven International Publishing, 2018)
The need to change towards a sustainable economy has propelled companies to collaborate in sustainability initiatives. Such initiatives, however, might be held against European competition law. This poses the question: can competition law be rebalanced so as to provide room for sustainability initiatives? In her inaugural lecture, the author argues that Euro pean competition law cannot remain isolated from broader societal considerations. To retain its legitimacy, competition law needs to respond to the changed societal situation. It needs to be ready for the future, so to continue to be acceptable to the European citizens. The argument is based on an insightful account of the changing roles of the State and the market in providing for the public interest. Set against the backdrop of globalisation and the need for a sustainable society, it is argued that companies and civil society also have an important role to play. The author does not shy away from moral questions of fairness, and shows how European competition law can balance the interests of well-functioning markets against supporting sustainability initiatives.--